Is the Apparent Degree of Fermentation a Reliable Estimator of Fermentability?. (2nd January 2019) - Huerta-Zurita, Ramon; Horsley, Richard D.; Schwarz, Paul B.
Abstract: The analysis of fermentability, or real degree of fermentation (RDF), involves the determination of real extract (RE) in a fermented sample. Considering that RDF analysis is expensive and time consuming, some researchers instead, report the apparent degree of fermentation (ADF). However, since the ADF calculation considers initial and final specific gravities of the fermented sample, variation in alcohol content could have an effect on ADF. This is especially true when samples with widely different backgrounds are tested, as is often the case during malting barley breeding. The objective of this research was to define the feasibility of using ADF for selecting and discriminating different samples in terms of fermentability. Additionally, different equations for calculating RE and original extract (OE) were compared and discussed. Results showed that ADF values change at different alcohol contents in samples with similar RDF, which could lead to the determination of false differences in relation to this trait. Our findings suggest that ADF is not a reliable indicator of fermentability for the discrimination of barley breeding samples. In addition, it was observed that OE and RE values, as calculated by the Balling Equation, can be over- or under-estimated depending upon the alcohol content of fermented samples.